Estudo de fertilizante organomineral granulado comercial composto por material lignocelulósico compostado de aterro industrial e monofosfato de amônio (MAP) - Sobreira, Henrique de Araujo (2025)
Organomineral fertilizers (FOM) are a sustainable alternative to conventional fertilization, combining the efficiency of minerals with the benefits of organic matter. This thesis investigates the release of phosphorus (P) in granulated organomineral fertilizers (FOG), prepared from the addition of composted waste from the pulp and paper industry, compared to the mineral base, monoammonium phosphate (MAP), both in water and soil. The fertilizers were characterized in their original form and modified with a diacetate cellulose (DAC) coating to control P availability. Characterization through scanning electron microscopy (SEM) and nitrogen adsorption/desorption analyses showed that MAP has a compact structure and low porosity. At the same time, FOG exhibits more significant heterogeneity and a larger surface area (0.37 m² g⁻¹ for MAP and 1.24 m² g⁻¹ for FOG) due to the presence of organic matter, confirmed by Fourier-transform infrared spectroscopy (FTIR) and thermogravimetric analyses (TG), where FOG demonstrated greater thermal stability due to the interaction between the organic fraction and the mineral material. In P release tests, temperature and time were determining factors, with both fertilizers releasing 77% of the available P in the first 4 hours; after 240 hours, the specific surface area of FOG increased 29 times, intensifying P release. The kinetics of P release from fertilizers show the burst effect, followed by pseudo-Fickian transport, as described by the Korsmeyer-Peppas model. For the fertilizers coated with DAC by spraying and immersion techniques, SEM images showed that the granules of FOG and MAP coated by immersion were homogeneous and thick, reducing the initial release of P and promoting gradual release. In contrast, this effect was diminished for FOG due to the interaction of the organic fraction with the coating, resulting in increased porosity. The Weibull model was suitable for the coated fertilizers, indicating Fickian diffusion as the primary release mechanism. In soil, the coated fertilizers showed lower initial P mobility, promoting controlled release over time, while MAP exhibited higher mobility due to its mineral composition. The results demonstrate the potential of coated organomineral fertilizers to optimize P release, reduce environmental impacts, and enhance agronomic efficiency, positioning FOG as a viable alternative to partially replace conventional mineral fertilizers, especially when associated with coating technologies.